The revolutionary : Samuel Adams - Schiff, Stacy (Little, Brown and Company, 2022)
"Thomas Jefferson asserted that if there was any leader of the Revolution, "Samuel Adams was the man." With high-minded ideals and bare-knuckle tactics, Adams led what could be called the greatest campaign of civil resistance in American history. Stacy Schiff returns Adams to his seat of glory, introducing us to the shrewd and eloquent man who supplied the moral backbone of the American Revolution. He employed every tool available to rally a town, a colony, and eventually a band of colonies behind him, creating the cause that created a country. For his efforts he became the most wanted man in America: When Paul Revere rode to Lexington in 1775, it was to warn Samuel Adams that he was about to be arrested for treason. In The Revolutionary: Samuel Adams, Schiff brings her masterful skills to Adams's improbable life, illuminating his transformation from aimless son of a well-off family to tireless, beguiling radical who mobilized the colonies"--